Perceptions of Dental Students toward Dentistry and Difficulties They Face during Preclinical Operative Dentistry Education - Dülger, Kıvanç; Bulut Eyüboğlu, Güneş (Journal of Dentistry Indonesia, 2022)
Objective: The aim of this study is to assess the attitudes of dental students toward dentistry and the difficulties they face during their preclinical operative dentistry education, especially its practical aspect. Methods: About 100 third-year dental students answered a paper-based survey questionnaire (response rate = 90.90%), which was prepared and distributed in April 2019. The data were analyzed using SPSS version 22 (IBM SPSS, Turkey), and a one-way ANOVA test was used to determine the students’ competence for patient treatment based on their difficulty scores. Results: No statistically significant relationship was identified between the participants’ difficulty scores and grade point averages (p > 0.05). The students who felt ready for their clinical dental education phase—due the following year—had statistically significant lower difficulty scores than those who felt incompetent and uncertain (p: 0.005; p < 0.05). Notably, there was no statistically significant difference in the difficulty scores (p > 0.05) between the participants who felt incompetent and uncertain. Conclusion: Dental practice plays an important role in preclinical operative dentistry education. Therefore, dental students should be adequately prepared for operative preclinical practice, which can be achieved by offering more preclinical practice through collaboration with educators.